The Nature Protection Aspect of the Black Sea Fish Myxosporean (Myxozoa, Myxosporea) Studies - Yurakhno, V.M. (Вестник зоологии, 2013)
The species composition and indices of the myxosporeans infecting fish from the different nature conservation Black Sea regions were considered on the base of the original investigations and literature data. Myxosporean inhabiting the Red Book fish hosts were investigated. The myxosporean species potentially pathogenic for the fish health were identified and epizootological situation was estimated. На основе оригинальных исследований и литературных данных рассмотрены видовой состав и показатели заражённости миксоспоридиями рыб из различных природоохранных регионов Чёрного моря. Исследованы миксоспоридии, встречающиеся в краснокнижных видах рыб-хозяев. Обозначены потенциально патогенные для здоровья рыб виды слизистых споровиков, оценена эпизоотологическая ситуация.